Biosorption of Copper(II) Ion From Aqueous Solutions Using Caucasian Fir (Abies nordmanniana (Stev.) Spach. subsp. nordmanniana) Cones - AKSAKAL, OZKAN; KAYA, YUSUF; SENGUL, MERYEM (Asian Journal of Chemistry, 2010)
In the present study the biosorption characteristics of Cu(II) ions from aqueous solution using the cone Caucasian fir biomass were investigated. Optimum biosorption conditions were determined as a function of initial metal ion concentrations, biomass dosage, pH and contact time. Caucasian fir cones exhibited the highest copper(II) uptake capacity at the initial pH value of 5.0 in 1 h, 6 g/L biomass dosage and initial copper(II) ion concentration of 50 mg/L. The removal of copper(II) from aqueous solution increased with pH and sharply decreased when pH of the solution was decreased. At the optimal conditions, copper(II) ion biosorption was decreased as the initial metal concentration increased. Freundlich and Langmuir models were applied to describe the biosorption isotherm of the metal ions by Caucasian fir biomass. Both models were found to exhibit good fits to the experimental data.